PENYIDIKAN TINDAK PIDANA PENCURIAN ARUS LISTRIK DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Mensa, Fradhil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Theft crime is one crime that often occur, particularly in the crime of theft of electric current. The number of reports regarding the crime of theft in various mass media both electronic and print media. Criminal offense of theft of electric current is usually done by several persons, from among the household users as well as from the business community. The background of the perpetrator committed the crime of theft of electric current, it is not connected with economic circumstances or level of income that low that theft of electric current because they do not have electricity in the house, but there are also actors who come from higher income levels who commit theft of electric current , Because it does not want to pay more than it should, when electricity usage that exceeds a predetermined electric power or agreed it is a criminal offense.The purpose of this study How the investigation of criminal theft of electric current in the jurisdiction of the resort city of Pekanbaru police, Are the obstacles faced in criminal investigations of theft of electrical current in the jurisdiction of the police and the resort city of Pekanbaru How are investigators in the criminal investigation of theft of electric current in the region the resort town of Pekanbaru police law.From this study it can be concluded that the process of settlement of criminal cases of theft of electric current in the Regional Law Pekanbaru City Police is to do a legal settlement peacefully. Barriers that occur in the process of criminal investigation of theft of electric current in the region Pekanbaru City Police Law, namely internal and external obstacles, internal barriers include police investigators limited personnel, lack of facilities, lack of police experts in handling criminal cases of theft of electric current, ekternalnya obstacles include the difficulty in summoning witnesses, require expert testimony because the complainant did kepolisi report shortly after the crime. Later efforts to overcome obstacles in the process of criminal offenses of theft of electric current in the region Pekanbaru City Police Law is internal efforts include increasing the number of personnel investigation team Pekanbaru City Police, the addition of patrol cars and vehicles belonging to Pekanbaru City Police, conduct specialized training for executing tasks Pekanbaru City Police Investigator for criminal cases of theft of electric current. External efforts include coordination between the Contracting Parties PT.PLN Police Pekanbaru, visited the residence domicile of witnesses, conduct peace efforts.Keywords: Investigation, crime, theft of